2020
DOI: 10.1002/mnfr.202000108
|View full text |Cite
|
Sign up to set email alerts
|

Bilberry Supplementation after Myocardial Infarction Decreases Microvesicles in Blood and Affects Endothelial Vesiculation

Abstract: Scope: Diet rich in bilberries is considered cardioprotective, but the mechanisms of action are poorly understood. Cardiovascular disease is characterized by increased proatherogenic status and high levels of circulating microvesicles (MVs). In an open-label study patients with myocardial infarction receive an 8 week dietary supplementation with bilberry extract (BE). The effect of BE on patient MV levels and its influence on endothelial vesiculation in vitro is investigated. Methods and results: MVs are captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 75 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, a study based on the United States Cancer Center Support Grant found that higher lignan consumption was inversely correlated with the risk of breast cancer among pre-and menopausal women (McCann et al, 2011). The results were supported by other meta-analysis studies that demonstrated that high levels of plant lignan consumption was strongly correlated with a reduction in postmenopausal breast cancer risk (Buck et al, 2010;Velentzis et al, 2009). Dietary lignans have also been implicated in the reduction of CVD risks in postmenopausal women (Sammartino et al, 2006).…”
Section: Health Benefits Of Non-nutritive Bioactives In Berriesmentioning
confidence: 74%
“…Furthermore, a study based on the United States Cancer Center Support Grant found that higher lignan consumption was inversely correlated with the risk of breast cancer among pre-and menopausal women (McCann et al, 2011). The results were supported by other meta-analysis studies that demonstrated that high levels of plant lignan consumption was strongly correlated with a reduction in postmenopausal breast cancer risk (Buck et al, 2010;Velentzis et al, 2009). Dietary lignans have also been implicated in the reduction of CVD risks in postmenopausal women (Sammartino et al, 2006).…”
Section: Health Benefits Of Non-nutritive Bioactives In Berriesmentioning
confidence: 74%
“…The findings showed that BE supplementation positively affected the MV profile in participants' blood and decreased extracellular vesicle release via a P2X7 receptor-dependent mechanism. The cardioprotective effect of blueberries has been proven [109]. The antioxidant properties of V. myrtillus may partly explain its ability to protect rats from doxorubicin (DOX)-induced cardiotoxicity.…”
Section: Cardiologymentioning
confidence: 99%
“…The bilberry group patients were also more successful in a 6 min walking test ( Arevström et al, 2019 ) The same group of patients was also evaluated for the presence of circulating microvesicles which are a marker of cardiovascular disease. It was found that bilberry extract improved the blood profile and reduced endothelial vesiculation ( Bryl-Górecka et al, 2020 ). Another clinical study showed that consumption of 150 g of frozen bilberries 3 times a week for 6 weeks led to a significant decrease in total cholesterol, LDL and triglycerides, and a favorable increase in HDL ( Habanova et al, 2016 ).…”
Section: Uses Of Vaccinium Myrtillus Lmentioning
confidence: 99%